THE EFFECTS OF OXIDATIVE STRESS ON PHENOLIC COMPOSITION AND ANTIOXIDANT METABOLISM IN CALLUS CULTURE OF COMMON DAISY - Pehlivan Karakas, Fatma; Cingoz, Gunce Sahin; Ucar Turker, Arzu (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Exogenous pretreatment of oxidative stress on callus cultures of Bellis perennis L. (common daisy) induced catalase (CAT), superoxide dismutase (SOD), total phenolic, total flavonoid, total protein and selected commercial phenolic compounds production and accumulation. Materials and Methods: The callus culture obtained from B. perennis pedicel explants was incubated on Murashige and Skoog medium (MS) containing 10 mM H2O2 or 0 mM H2O2 (for control group) for 10 hours. Twenty phenolic compounds (apigenin, caffeic acid, p-coumaric acid, gallic acid, genistein, kaempferol, luteolin, myricetin, procyanidin-C1, quercetin, rutin hydrate, vanillic acid, ferulic acid, salicylic acid, sinapic acid, chlorogenic acid, hesperedin, naringenin, rosmarinic acid and isorhamnetin) were detected by LC-ESI-MS/MS analysis in methanolic extracts of 10 mM H2O2 and control treatments. Results: A predominant phenolic compound was chlorogenic acid followed by rutin hydrate, caffeic acid, luteoline, isorhamnetin, quercetin, myricetin, apigenin, p-coumaric acid and kaempferol. No gallic acid, genistein, procyanidin-C1, vanillic acid, sinapic acid, hesperidin and naringenin were detected in H2O2 treatment and control groups of B. perennis. The total phenolic contents estimated were in the order of H2O2 treatment (285.36 μg/g dw) and control (220.79 μg/g dw) groups. The biosynthesis and accumulation of kaempferol, myricetin, quercetin and isorhamnetin were only determined in H2O2 treatment callus materials. The H2O2 pretreatment clearly showed in a raise in enzymatic and non-enzymatic antioxidant activities. Finally, a significant positive correlation between phenolic accumulation and comprehensive activities of CAT, SOD, total phenolic, total flavonoid and proline was accessible. Conclusion: The present results suggest that using H2O2 as an elicitor or a stimulant plays a significant enhancement role in special phenolic molecules biosynthesis and activation of antioxidant metabolism on callus cultures of B. perennis.